Wrażliwość modelu MKMV ze względu na metodę estymacji wzrostu wartości aktywów - Wójcicka, Aleksandra (The Vulnerability of MKMV Model with Regard to the Estimation Method of the Expected Return on Assets, 2008)
In the paper the vulnerability of MKMV model with regard to the estimation method of the expected return on assets (µ) was tested. The evaluation of µ is carried on the basis of CAPM where in turn the equity premium is the most difficult parameter to evaluate. The results obtained show that regardless of the equity premium estimation method the parameter µ reaches similar levels. Nevertheless, its influence on the probability of default (PD) is significant - on average the levels of PD are lower by half if we include µ. Therefore, it is absolutely incomprehensible why it is left out by the practitioners. In further research another models of the expected return on assets estimation should be tested as well as their influence on the credit risk level.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 182-189